MODELLING OF DETERIORATED ELECTRICAL STEEL PROPERTIES DUE TO LASER CUTTING PROCEDURE - Ilgaz, Mehmet Alp; Corovic, Selma; Makuc, Danilo; Alic, Alen; Vukotic, Mario; Miljavec, Damijan (Gebze Teknik Üniversitesi, 2020)
The quality and efficiency of electrical machines are key factors towards improvement of the drive performance. Manufacturing processes have a significant impact on the efficiency of electrical machines. There are different manufacturing techniques such as mechanical cutting, laser cutting, electrical discharge machining etc. Each cutting techniques may cause a deformation near edges of the cutting area that may severely affect the properties of the B-H curve of the ferromagnetic materials. Thus it is important to predict approximately the extension of the damaged area. In this study we have developed an approach based on finite element method using COMSOL Multiphysics simulation software to evaluate the deformation caused by laser cutting on the edges of the ferromagnetic material.
Keywords: Electrical Engineering; Elektrik Mühendisliği